College education of elementary school teachers: the case of mathematics - Alpízar-Vargas, Marianela (2019)
This article describes the curricula offered by state and private universities in Costa Rica to obtain a teaching degree in cycles I and II of elementary education. The study is qualitative and descriptive. Curricula from different universities were reviewed, and coordinators of related programs and math professors from those universities were interviewed. The analysis revealed a wide variety of study programs to train elementary school teachers with no general guidelines and little control. Therefore, there are no regulations in Costa Rica for these programs’ purposes, duration, content or teacher profile, which could affect math education in elementary schools since teachers come from programs with different emphasis